49th AIAA/ASME/SAE/ASEE Joint Propulsion Conference 2013
DOI: 10.2514/6.2013-4177
|View full text |Cite
|
Sign up to set email alerts
|

The Utilization of Launch Vehicles Core Stages and Propellant Depots for Human Space Exploration

Abstract: A crewed mission to a near earth asteroid would yield both scientific and engineering advancements. Visiting one or several of these objects would not only validate technologies that could later be used to visit the Moon or Mars, but would also develop our scientific understanding of asteroids and the solar system. This study proposes an architecture that represents a paradigm shift in the way space exploration is conducted. By including the commercial space industry in this mission and encouraging competition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Previous studies have identified the potential for the intersection of chemical propulsion, in-space storage, and propellant transfer to enable missions to Mars [4][5][6][7] . These studies have considered the application of those three capabilities to supporting Mars missions similar to the Design Reference Architecture 5.0 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have identified the potential for the intersection of chemical propulsion, in-space storage, and propellant transfer to enable missions to Mars [4][5][6][7] . These studies have considered the application of those three capabilities to supporting Mars missions similar to the Design Reference Architecture 5.0 8 .…”
Section: Introductionmentioning
confidence: 99%